THE EFFECT OF REGIONAL ORIGINAL REVENUE, CAPITAL EXPENDITURE AND GENERAL ALLOCATION FUNDS ON THE FINANCIAL PERFORMANCE OF DAPIL 1 DISTRICT CITY OF WEST SUMATRA PROVINCE - M. Raja Rafli; Marzuki; Ristati; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to determine the Regional Original Income, Capital Expenditure and General Allocation Funds on the Financial Performance of the District 1 Regency/City of West Sumatra Province. The data collection technique uses secondary data in the form of financial reports accessed through the official website.www.djpk.kemenkeu.go.id. The collected data was processed using the EViews 12 program. The population used in this study was the Electoral District 1 of the Regency/City of West Sumatra Province. The sample selection technique used purposive sampling technique and obtained 11 regions for 7 years with a total of 77 sample data obtained. The data analysis method used in this study was panel data regression analysis. The results of the study found that local revenue had an effect on regional financial performance, capital expenditure had no effect on regional financial performance and general allocation funds had a negative effect on regional financial performance of Electoral District 1 of the Regency/City of West Sumatra Province.